2010
DOI: 10.1002/anie.201001684
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Nanoscale Films of Metal–Organic Frameworks By Room‐Temperature Gel‐Layer Synthesis

Abstract: Metal-organic frameworks (MOFs) assembled from organic building blocks and metal-based connectors have attracted much interest owing to their large pores and their enormous structural diversity. Particularly, the generation of homogeneous thin films of MOFs is highly desirable in view of potential applications including chemical sensors, catalysts, and also optical devices. Several elegant examples of MOF film growth have recently been reported (see below), but a general and convenient method for the synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
92
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 137 publications
(92 citation statements)
references
References 43 publications
0
92
0
Order By: Relevance
“…The R a of MIL-101(Cr), NH 2 -MIL-101(Cr), and NO 2 -MIL-101(Cr) thin films are only 3.4, 3.0, and 4.2 nm, respectively. The R q of them are 4.4, 3.8, and 5.5 nm, which are smaller than those of MOF-based thin films in previous reports [18,34,35]. For instance, Demessence et al [18] reported that the root-mean-square roughness of MIL-101(Cr) optical thin films was calculated to be around 12 nm (nearly half of the MOF NP diameter).…”
Section: Fabrication Of Mof-based Optical Thin Filmsmentioning
confidence: 75%
See 1 more Smart Citation
“…The R a of MIL-101(Cr), NH 2 -MIL-101(Cr), and NO 2 -MIL-101(Cr) thin films are only 3.4, 3.0, and 4.2 nm, respectively. The R q of them are 4.4, 3.8, and 5.5 nm, which are smaller than those of MOF-based thin films in previous reports [18,34,35]. For instance, Demessence et al [18] reported that the root-mean-square roughness of MIL-101(Cr) optical thin films was calculated to be around 12 nm (nearly half of the MOF NP diameter).…”
Section: Fabrication Of Mof-based Optical Thin Filmsmentioning
confidence: 75%
“…For instance, Demessence et al [18] reported that the root-mean-square roughness of MIL-101(Cr) optical thin films was calculated to be around 12 nm (nearly half of the MOF NP diameter). The root-mean-square surface roughness of gel-layer synthesized Fe-MIL-88B_NH 2 thin film was 5-9 nm (from atomic force microscope images) [34]. These results suggest that the fabricated MOF optical thin films are of high quality.…”
Section: Fabrication Of Mof-based Optical Thin Filmsmentioning
confidence: 77%
“…The surfactant N-ethyl perfluorooctylsulfonamide (N-EtFOSA) forms microemulsions in a solvent mixture of the IL 1,1,3,3-tetramethylguanidinium acetate (TMGA) and SCCO 2 , as the interactions between CO 2 and the fluorocarbon tails of the surfactants are strong. 53,54 In a standard synthesis procedure, Zn(NO 3 ) 2 , 1,4-benzenedicarboxylic acid (H 2 bdc) and N-EtFOSA were added to TMGA and heated in a high-pressure cell under 16.8 MPa CO 2 pressure at 80 C for 48 h. Transmission electron microscopy (TEM) images (Fig. 2) show nanoparticles of roughly 80 nm diameter with a uniform size distribution and a well ordered system of mesopores.…”
Section: Microemulsion Synthesismentioning
confidence: 99%
“…Schoedel et al used a thin poly(ethylene oxide) gel layer deposited on a gold slide as a storage medium to confine a high concentration of metal ions near to a nucleating surface functionalized with self-assembled monolayers. 85 Very homogeneous PCP thin films were obtained in unique crystal orientation on COOH-functionalized SAMs after synthesis in the presence of the organic linker. Other groups reported the deposition of [Cu 3 (btc) 2 ] monodisperse crystals in patterns down to the single-crystallite level by the use of soft lithographic 86 and inkjet printing techniques.…”
Section: Metal Ion N Ligand Dicarboxylatementioning
confidence: 99%